Free and Unfree Labor in Atlantic and Indian Ocean Port Cities (Seventeenth–Nineteenth Centuries). (26th March 2019) - Brandon, Pepijn; Frykman, Niklas; Røge, Pernille
Abstract: Colonial and postcolonial port cities in the Atlantic and Indian Ocean regions functioned as crucial hubs in the commodity flows that accompanied the emergence and expansion of global capitalism. They did so by bringing together laboring populations of many different backgrounds and statuses – legally free or semi-free wage laborers, soldiers, sailors, and the self-employed, indentured servants, convicts, and slaves. Focusing on the period from the seventeenth to the mid-nineteenth centuries, a crucial moment in the establishment of the world market, the transformation of colonial states, and the reorganization of labor and labor migration on a transoceanic scale, the contributions in this special issue address the consequences of the presence of these "motley crews" on and around the docks and the neighborhoods that stretched behind them. The introduction places the articles within the context of the development of the field of Global Labor History more generally. It argues that the dense daily interaction that took place in port cities makes them an ideal vantage point from which to investigate the consequences of the "simultaneity" of different labor relations for questions such as the organization of the work process under developing capitalism, the emergence of new forms of social control, the impact of forced and free migration on class formation, and the role of social diversity in shaping different forms of group and class solidarity. The introduction also discusses the significance of the articles presented in this special issue for three prevailing but problematic dichotomies in labor historiography: the sharp borders drawn between so-called free and unfree labor, between the Atlantic and the Indian oceans, and the pre-modern and modern eras.